2016
DOI: 10.1016/j.jaci.2015.12.1330
|View full text |Cite
|
Sign up to set email alerts
|

Clonal expansion of CD4+ cytotoxic T lymphocytes in patients with IgG4-related disease

Abstract: Background IgG4-related disease (IgG4-RD) is a systemic condition of unknown etiology, characterized by highly fibrotic lesions with dense lymphoplasmacytic infiltrates. CD4+ T cells constitute the major inflammatory cell population in IgG4-RD lesions. Objective We used an unbiased approach to characterize CD4+ T cell subsets in IgG4-RD subjects based on their clonal expansion and their ability to infiltrate affected tissue sites. Methods We used flow cytometry to identify CD4+ effector/memory T cells (TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
269
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 314 publications
(291 citation statements)
references
References 61 publications
(77 reference statements)
15
269
4
3
Order By: Relevance
“…42 Subsequent studies analyzing the T cell repertoire from subjects with active IgG4-RD who also had a history of atopy documented no clonal expansions of Th2 cells but rather indicated diverse polyclonality, consistent with a lifetime of exposure to environmental allergens. 43 In contrast, the same study detected a highly-restricted repertoire in a separate T-cell population: cytotoxic CD4 + T-cells (CD4 + CTLs). 43 …”
Section: Th2 Cells Atopy and Igg4-rdmentioning
confidence: 94%
“…42 Subsequent studies analyzing the T cell repertoire from subjects with active IgG4-RD who also had a history of atopy documented no clonal expansions of Th2 cells but rather indicated diverse polyclonality, consistent with a lifetime of exposure to environmental allergens. 43 In contrast, the same study detected a highly-restricted repertoire in a separate T-cell population: cytotoxic CD4 + T-cells (CD4 + CTLs). 43 …”
Section: Th2 Cells Atopy and Igg4-rdmentioning
confidence: 94%
“…Indeed, the effectiveness of B cell depletion therapy in IgG4-RD suggests that B lymphocytes and other cells of this lineage play an important pathological role, probably via their interaction with CD4 + cytotoxic T lymphocytes (CTL) serving as effective antigen-presenting cells and/or through the secretion of B cell-derived growth factors [42, 43]. …”
Section: Pathophysiologymentioning
confidence: 99%
“…The recent characterisation of a clonally expanded population of CD4 + CTL in both the peripheral blood and fibrotic lesions of IgG4-RD patients suggests that these cells are indeed central to the disease pathogenesis [41, 43, 49]. Mattoo et al demonstrated that CD4 + CTL cells which also expressed signalling lymphocytic activation molecule F7 (SLAMF7) were expanded in patients with IgG4-RD, and these cells expressed granzyme B, perforin, IL-1β, TGF-β and IFN-γ, which may be important mediators of tissue damage [43]. Rituximab-induced clinical remission was associated with a reduction in the number of these CD4 + CTL, but had minimal or no effect on the frequency and number of CD4 + GATA3 + Th2 phenotype cells or CD4 + CD25 + Foxp3 + regulatory T cells [49].…”
Section: Pathophysiologymentioning
confidence: 99%
“…The clonally expanded population of CD4+ cytotoxic T lymphocytes in both the peripheral blood and the fibrotic lesions of IgG4-RD patients suggests that these cells are central to the disease. Mattoo et al [7] reported that IL-1, TGF-beta, and interferon-gamma expressed by these cells are all potentially important mediators of the fibrosis which is a dominant part of the histopathology in IgG4-RD [7]. In the same work, the authors demonstrated that the number of these cells decreased concomitantly with a clinical response to rituximab therapy, suggesting a contributory role for these CD4+ cytotoxic T cells in the pathogenesis of IgG4-RD.…”
Section: Discussionmentioning
confidence: 99%